How We See Science Communication Process and Problems - Richard L. Lee (Journal of Applied Communications, 1979)
My concerns are pragmatic. As head of an agricultural experiment station information unit one of my major concerns is maintaining credibility with the different audiences we work for, with, and under. Included are 1) administrators; 2) scientists; 3) mass media representatives; and 4) the general public. (Papers from the National Agricultural Science Information Conference, Ames, Iowa.)